Sebaran tingkat kemiskinan dan tingkat akses air bersih di Sumatera Selatan - Desri Yesi; Oktaf Juairiyah (Dinamika Lingkungan Indonesia, 2021)
The poverty level and the level of access for cleaning water are two interesting variables to analyze. One type of feasible analysis was used scatter diagram. South Sumatra Province with its 17 municipalities has different characteristics in terms of poverty levels and access to clean water for the people. Overall, using the scatter diagram, in 2018 the areas with low poverty levels however high levels of access to clean water (Quadrant I) were Lahat and Penukal Abab Lematang Ilir Regency. The regions with low levels of access to clean water and low levels of poverty (Quadrant II) are Empat Lawang, Banyuasin, Ogan Komering Ulu  Selatan and Prabumulih. The areas with high levels of access to clean water and high poverty (Quadrant III) are Musi Rawas Utara, Musi Banyuasin, Ogan Komering Ilir,  Musi Rawas and Ogan Ilir Regency. The areas with low levels of access to clean water and high poverty (Quadran IV) are Lahat and Penukal Abab Lematang Ilir regency.